The role of Nigerian youths in re-branding Nigeria (2010)
Nigeria as a political entity, in recent times, has been engulfed by nefarious activities of the youths, an unarguably important segment of the society. Such vices include, drug abuse, lesbianism, homosexuality, internet fraud, religious violence, political assassination, cultism, examination malpractices, organised militancy and of course the latest immoral and unethical attempt of terrorism made by a Nigerian youth, Abdul-Mutallab. The unwholesome activities highlighted above have greatly dented Nigeria’s image among the comity of nations, hence the quest for positive transformation of her image by the Federal Government in the name of re-branding. This paper therefore argues that the prevalence of all forms of societal decadence in Nigeria was a reaction to the corrupt and inefficient leadership as well as parental negligence of this vital segment of the society.